A biocompatible reverse thermoresponsive polymer for ocular drug delivery. (1st January 2019) - Balachandra, Asitha; Chan, Elsa C.; Paul, Joseph P.; Ng, Sze; Chrysostomou, Vicki; Ngo, Steven; Mayadunne, Roshan; van Wijngaarden, Peter
Abstract: Age-related macular degeneration (AMD) is a leading cause of vision loss, the treatment of which may require monthly intravitreal injections. This is a burden on patients and health services, and new delivery modalities that reduce injection frequency are required. To that end, we investigated the suitability of a novel reverse thermoresponsive polymer (RTP) as an ocular drug-delivery vehicle. In this work, we detail the structure and synthesis of a novel RTP, and determine drug release curves for two drugs commonly used in the treatment of AMD, bevacizumab and aflibercept. Biocompatibility of the RTP was assessed in vitro in human and rat cell lines and in vivo following intravitreal injection in rats. Bevacizumab demonstrated a more appropriate release profile than aflibercept, with 67% released within 14 days and 78% released in total over a 183-day period. No toxic effects of RTP were seen in human or rat cells in up to 14 days of co-culture with RTP. Following intravitreal injection, intraocular pressure was unaffected by the presence of RTP and no changes in retinal function or structure were observed at 1 week or 1 month post-injection. RTP injection did not cause inflammation, gliosis or apoptosis in the retina. This work demonstrates the potential suitability of the novel RTP as a sustained-release vehicle for ocular drug delivery for anti-neovascular therapies. Optimization of polymer chemistry for optimal drug loading and release is needed.